Svenska hushålls vedarbete : en fallstudie i Umeåregionen - Moe, Daniel (SLU/Dept. of Forest Resource Management, 2007)
In Sweden there are 354 000 private individuals owning forest. Of these forest owners there are at least two thirds that are self-employed, which means that about 215 000 forest owners conduct some kind of work in their own forest. Those numbers do not refer to firewood production, but every year 7.3 million piled cubic meters of firewood are used for heating Swedish households. This implies that many households are also producing firewood.